An effectiveness study on digital game-based learning model of hajj for da’wah dissemination: a case study on secondary school students - Nur Nazihah Rahim (2022)
Digital technologies in Industry 4.0 have been enthusiastically discussed because it becomes a transforming agent towards societies and economy. Such transformation can have an impact and influence towards the formation of society’s behaviour. Digital games are considered one of the best new media tools for fostering positive behaviour if it integrates a spiritual quotient and contains an Islamic message. Through this medium, da’wah can be effectively delivered. In today’s world, da’wah needs to be more creative in order to attract more people in learning Islam. Thus, digital game is a good platform for disseminating da’wah besides it is suitable for use as Teaching Aids (TA) for the students in understand more about a particular learning topic. However, students have difficulty mastering the topic of Lambaian Kaabah because there are many concepts of hajj that need to be understood in the Islamic Studies subject. As a tool for Teaching & Learning (T&L) in the classroom, Digital Game-Based Learning (DGBL) is the best option available. Thus, a specific model of DGBL in producing an appropriate DGBL corresponding to the nature of da’wah dissemination through digital technology on student performance should be proposed. This research used a developmental research design in designing the model and used a quantitative method (survey towards secondary school students in Form 4 and expert test for Islamic Studies Teachers, Designers, and Islamic Officers). This research used purposive sampling to the students. From the result obtained, the proposed model is significantly validated with the main feature of narrative design, including new constructs (i.e content and process). DGBL can be one of the alternative methods of da’wah dissemination and expressing the beauty of Islam through a creative and attractive approach. The game contents (specifically in the form of da’wah and Islamic teaching) combined with a good design will lead to more interesting and beneficial games for players. Digital games are not intended to replace the da’wah that was done by the Prophet Muhammad (PBUH), but nevertheless it should be used in accordance with the current situation so that Islamic da’wah can be conveyed more effectively.